Introduction to environmental modelling, by W.G. Gray and G.A. Gray, 2017 - Bronikowska, Małgorzata (Geologos, 2022)
Review: Introduction to environmental modelling, by W.G. Gray and G.A. Gray, 2017. Cambridge University Press, Cambridge, UK. 625 pages. Paperback: price €42, Kindle: price €34, ISBN 9781107571693.